Parcours d’une œuvre culturelle lobi du Burkina Faso : le bitebo d’Henri Labouret - Saga Ouiya (Les Cahiers de l'École du Louvre)
The bitebo is a wooden stool from Burkina Faso. It was collected between 1912 and 1920, during the French colonial period, by the colonial administrator Henri Labouret. It was against a backdrop of instability, characterised by revolts, resistance and so-called pacification campaigns, that Labouret acquired the bitebo and later gave it to the Musée d’Ethnographie du Trocadéro. The object is a true reflection of the cultural identity of the Lobi people. The stool can be used by both men and women. It fulfils three major functions: weapon of proximity, ritual object and tool. Its collection and entry into the museum coincided with the discovery and dissemination of Lobi art in the West.